La responsabilidad social corporativa como estrategia empresarial y su integración en el cuadro de mando integral (2019)
This paper presents a literature review that focuses on the concept of corporate social responsibility as a business strategy and its integration into the comprehensive scorecard. Initially, the evolution and development of the comprehensive scorecard is reviewed, from its origin to The last modifications made by the business and academic world, subsequently considered three case studies of organizations that implemented this model of integration of corporate social responsibility to their comprehensive scorecard and obtained a significantly positive impact on their processes.